2008
DOI: 10.1038/oby.2007.86
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Weight Management Program on the Determinants and Prevalence of Metabolic Syndrome

Abstract: objective: As prevalence of obesity and metabolic syndrome (met synd) rises, establishing effective, community-based treatments is imperative. Our investigation sought to evaluate and report the effect of a weight management program on the prevalence and determinants of met synd, and the effect of participation level. Methods and Procedures: Between 10 July 2001 and 17 November 2005, 339 of 574 individuals enrolled in and completed our 6-month weight management program at the McConnell Heart Health Center in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Earlier observational (uncontrolled, non-randomized) studies suggested that lifestyle change programmes aiming at weight loss not only reduce weight but also positively affect the determinants and prevalence of MetS [12,13] and improve quality of life [14]. A systematic review has also shown that motivating MetS patients to maintain improved lifestyles is a key element in achieving a reduction in MetS components [15] and more recently, third-wave cognitive behaviour therapies (CBTs) including dialectical behavioural therapy, schema therapy, acceptance and commitment therapy, acceptance-based behavioural treatment, mindfulness-based cognitive behavioural treatment or compassion-focused therapy have been introduced [16].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier observational (uncontrolled, non-randomized) studies suggested that lifestyle change programmes aiming at weight loss not only reduce weight but also positively affect the determinants and prevalence of MetS [12,13] and improve quality of life [14]. A systematic review has also shown that motivating MetS patients to maintain improved lifestyles is a key element in achieving a reduction in MetS components [15] and more recently, third-wave cognitive behaviour therapies (CBTs) including dialectical behavioural therapy, schema therapy, acceptance and commitment therapy, acceptance-based behavioural treatment, mindfulness-based cognitive behavioural treatment or compassion-focused therapy have been introduced [16].…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure and triglycerides are components of metabolic syndrome. Many studies23,28 have shown that community-based intervention programs could affect metabolic parameters such as blood pressure, triglycerides, low-density lipoprotein, and HDL concentration. The favorable effects on lipids (with a low-carbohydrate diet) and on glycemic control (with the Mediterranean diet) suggest that personal preferences and metabolic considerations may be used to tailor individualized dietary interventions 29…”
Section: Discussionmentioning
confidence: 99%
“…The major weight-related behaviors in late-adolescence are snacking and late-night eating [26] .Further more, a study on twins showed that night-time eating was significantly more common in obese subjects than in subjects with normal weight [27] . Because awareness of weight control is itself beneficial for the prevention of MetS [28] and our workers who gained excessive weight tended to snack in addition to regular meals, education and reminders of healthy dietary behaviors for employees are essential for MetS management in workplaces. Dietary behavior is an important but complex issue in surveys concerning MetS development [29,30] .…”
Section: Discussionmentioning
confidence: 99%